2022
DOI: 10.4103/jfmpc.jfmpc_2382_21
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of fluoride uptake in soil and staple food crops produced in highly fluoridated and non-fluoridated regions of Raichur District, Karnataka

Abstract: Background and Aim: A staple food crops have varied role in diet of people living in particular regions of world; hence, it is critical to recognize their productivity. Therefore, the purpose of this study was to estimate fluoride concentration in staple food crops grown in highly fluoridated and non-fluoridated regions and its correlation with soil. Method: Total 36 samples were collected of which 18 samples consisting of each three samples of rice, redgram and jowar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Additionally, He et al [118] emphasized that in regions with brick kiln sites, the distribution of F − dust is primarily influenced by topological and meteorological conditions. Apart from the aforementioned factors, a recent study by Havale et al [119] revealed that the crop Jowar (sorghum) contains molybdenum, which can retain F − and reduce copper retention. Similarly, Khandare and Rao [120] emphasized adding molybdenum and aluminum, which reduced F − uptake by coriander plants.…”
Section: Occurrence Of Fluoride In Soil-plant Systemmentioning
confidence: 99%
“…Additionally, He et al [118] emphasized that in regions with brick kiln sites, the distribution of F − dust is primarily influenced by topological and meteorological conditions. Apart from the aforementioned factors, a recent study by Havale et al [119] revealed that the crop Jowar (sorghum) contains molybdenum, which can retain F − and reduce copper retention. Similarly, Khandare and Rao [120] emphasized adding molybdenum and aluminum, which reduced F − uptake by coriander plants.…”
Section: Occurrence Of Fluoride In Soil-plant Systemmentioning
confidence: 99%